Accounting Information System and Computerisation: A Conceptualisation - Collins C. Ngwakwe (International Review of Management and Marketing, 2022)
This paper highlights the computerisation fundamentals of accounting information system through accounting software application. It presents the layers of computerisation, which are pivotal to the application of accounting software, namely the hardware, the application, and system software. Furthermore, it highlights accounting software with selected examples from the Sage Accounting Software and notes significant advantage of applying the accounting software into accounting operations. These include amongst others integration of different items and different segments, speed, reliability, volume, storage, virtual, and real-time concurrent operations. It highlights nascent threat to computerisation and remote accounting processing, namely the ransom-ware cyber-attack. Therefore, the development of new anti-cyber-attack accounting software becomes very pertinent.